National down syndrome patient database: Insights from the development of a multi‐center registry study. (6th August 2015) - Lavigne, Jenifer; Sharr, Christianne; Ozonoff, Al; Prock, Lisa Albers; Baumer, Nicole; Brasington, Campbell; Cannon, Sheila; Crissman, Blythe; Davidson, Emily; Florez, Jose C.; Kishnani, Priya; Lombardo, Angela; et al.
<x xml:space="preserve">Abstract</x> The Down Syndrome Study Group (DSSG) was founded in 2012 as a voluntary, collaborative effort with the goal of supporting evidenced‐based health care guidelines for individuals with Down syndrome (DS). Since then, 5 DS specialty clinics have collected prospective, longitudinal data on medical conditions that co‐occur with DS. Data were entered by clinical staff or trained designees into the National Down Syndrome Patient Database, which we created using REDCap software. In our pilot year, we enrolled 663 participants across the U.S., ages 36 days to 70 years, from multiple racial and ethnic backgrounds. Here we report: (i) the demographic distribution of participants enrolled, (ii) a detailed account of our database infrastructure, and (iii) lessons learned during our pilot year to assist future researchers with similar goals for other patient populations. © 2015 Wiley Periodicals, Inc.